2014
DOI: 10.1177/1524839914524958
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Physical Activity in Rural Midwestern Adults

Abstract: Qualitative research can be used to examine multiple factors associated with physical activity and help practitioners identify language used by the rural adult population when discussing this behavior. Three focus groups were conducted among 19 residents of multiple towns in a rural Midwestern county to examine the language and influences on rural physical activity. Focus group members were asked to define physical activity, exercise, community, and neighborhood. They were asked about the activities they engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…In comparison, the state of Iowa is 94% white and 50.4% female. 16 Approximately 56 % were classified as overweight or obese according to their BMI (> 25), which is lower than the state average of 63 %. 18 …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In comparison, the state of Iowa is 94% white and 50.4% female. 16 Approximately 56 % were classified as overweight or obese according to their BMI (> 25), which is lower than the state average of 63 %. 18 …”
Section: Resultsmentioning
confidence: 91%
“…Prior focus groups with rural adults revealed that unpaved/gravel/dusty roads were common in this area, making it difficult to ride bicycles on them. 16 In addition, these roads did not contain shoulders, 16 which may have contributed to perceived feelings of the roads being unsafe for PA use. Participants in this study identified PA resources they were aware of and used in their county, and while awareness of the resources was high, use of the resources was not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published evidence supports the facilitating elements of safety and support. Chrisman, Nothwehr, Yang, and Oleson (2015) conducted three focus groups among 19 rural residents and concluded that safe communities, low crime rate, as well as low traffic rates, influenced physical activity. Chrisman et al also reported that older adults living in a perceived safe neighborhood were twice as likely to be physically active.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one recent qualitative study of older adults, Clancy, Balteskard, Perander, and Mahler (2015) concluded that in the experience of falls and falling, “participants’ stories reveals life courage and endurance and is more about getting up, staying up, and moving on than falling down.” (p. 9). Several studies have reported that older adults perceived adverse weather including ice, cold, snow as well as extreme heat as barriers to participating in physical activity (Chrisman et al, 2015; Marquez et al, 2014; Witcher et al, 2007). Also related to weather in rural communities, Chrisman et al (2015) found that loose gravel and muddy roads inhibited physical activity among adults in the rural Midwest USA.…”
Section: Discussionmentioning
confidence: 99%